2013
DOI: 10.1002/ange.201307976
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell‐Structured CNT@RuO2 Composite as a High‐Performance Cathode Catalyst for Rechargeable Li–O2 Batteries

Abstract: A RuO 2 shell was uniformly coated on the surface of core CNTs by a simple sol-gel method, and the resulting composite was used as a catalyst in a rechargeable Li-O 2 battery. This core-shell structure can effectively prevent direct contact between the CNT and the discharge product Li 2 O 2 , thus avoiding or reducing the formation of Li 2 CO 3 , which can induce large polarization and lead to charge failure. The battery showed a high round-trip efficiency (ca. 79 %), with discharge and charge overpotentials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 31 publications
1
71
0
Order By: Relevance
“…Wang et al [36] developed a MnCo2O4-graphitic carbon hybrid material as the non-precious metal catalyst, which delivers a lower overpotential (0.8 V) and a cut-off capacity of 1000 mA h g −1 for 40 cycles. On this base, Jian et al [37] further reduced the overpotential for Li-O2 reactions to 0.72 V by using carbon nanotubes (CNTs) supported RuO2 shells as the cathode catalyst. Xu et al [38] also demonstrated that the rate capability and lifespan of Li-O2 batteries can be significantly improved by tailoring the deposition behavior and morphology of the discharge products on a Pd-loaded hollow carbon air cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [36] developed a MnCo2O4-graphitic carbon hybrid material as the non-precious metal catalyst, which delivers a lower overpotential (0.8 V) and a cut-off capacity of 1000 mA h g −1 for 40 cycles. On this base, Jian et al [37] further reduced the overpotential for Li-O2 reactions to 0.72 V by using carbon nanotubes (CNTs) supported RuO2 shells as the cathode catalyst. Xu et al [38] also demonstrated that the rate capability and lifespan of Li-O2 batteries can be significantly improved by tailoring the deposition behavior and morphology of the discharge products on a Pd-loaded hollow carbon air cathode.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed replacement by Li-O 2 batteries still faces several technical challenges such as large voltage hysteresis, low round-trip efficiency and short cycle life [4][5][6]. Intensive research efforts towards better understanding of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) mechanisms, and the design principles of highly efficient ORR & OER catalysts are critical in improving battery performance [7][8][9][10]. Different from the intercalation mechanism in LIBs, Li-O 2 batteries are based on an electrocatalytic mechanism for both ORR and OER processes, where "electro" emphasizes the essentially smooth transportation for electrons, and "catalytic" indicates the necessity of catalysts with intrinsically high activity.…”
Section: Introductionmentioning
confidence: 99%
“…For the scale-up production of next-generation bifunctional catalysts in commercial MABs, low costs, high bifunctional activities, and good stability are strongly desired. In terms of material cost and availability, noble metals are being replaced by low-cost materials such as transitional metals, oxide, nitrides, carbides, sulfides, β-FeOOH, Fe phthalocyanine, and conducting polymers to Table 5 Electrochemical performance for typical metal-free carbon-composited bifunctional catalysts as air-electrode materials in the tested MABs rLOB [183] composite with carbon to enhance bifunctional activities and stability. With the rapid development of nanotechnologies and related sciences, processing techniques are becoming more facile in the fabrication of non-noble metal-based and metalfree bifunctional catalysts in scale-up productions.…”
Section: Other Carbon-based Ternary Compositesmentioning
confidence: 99%